Quality evaluation of the physical properties, phytochemicals, biological activities and proximate analysis of nine Saudi date palm fruit varieties - Abdul-Hamid, Nur Ashikin; Mustaffer, Nur Hafizah; Maulidiani, M.; Mediani, Ahmed; Ismail, Intan Safinar; Chau, Ling Tham; Abas, Faridah (Elsevier, 2020)
The date palm fruit (Phoenix dactylifera) is one of the earliest crops to be cultivated in the Middle East. Many varieties of dates are available and being marketed at various price ranges. However, there is no standardized approach available to verify the quality of Saudi date palm fruits. The current study aimed to assess the variations in the quality of different varieties of Saudi dates on the basis of the metabolite composition, proximate analysis, physical characteristics and biological activities. Nine date palm varieties Berni, Halaoua, Shalabi, Sogaai, Sukkari, Nebtat Ali, Anbara, Ajwa and Medjoul were evaluated via the Proton Nuclear Magnetic Resonance (1H NMR) based metabolomics approach. The DPPH and nitric oxide (NO) scavenging abilities, NO inhibition via the cell-based approach and total phenolic content (TPC) were determined. The physical features including dimension, seed/weight ratios and color variation also were evaluated. The proximate composition was carried out using the protocol ascribed by AOAC method. Metabolomics approach was successfully being applied in discriminating date palm varieties. Un-targeted metabolite profiling was achieved based on the acquired NMR data. Different trend of biological activities were displayed. The Ajwa dates which was the smallest, shortest in length and darkest colored Saudi date palm fruit demonstrated the highest percentage of NO inhibition/scavenging. Based on the variation in physical features, biological activities, metabolites content and proximate analysis, no noticeable correlation were observed between the market price and Saudi date palm variety qualities.